الرواية التاريخية بين الموضوعية والفنية عند علي أحمد باكثير وجرجي زيدان = Historical novels between objectivity and art according to Ali Ahmad Bakathir and Jurji Zaydan = Novel sejarah antara objectiviti dan nilai artistik mengikut pandangan Ali Ahmad Bakathir dan Jurji Zaydan - Hussein, Nasr El Din Ibrahim Ahmed; Samae, Abdul Halim (Research Management Centre, International Islamic University Malaysia (IIUM), 2019)
تسعى هذه الدراسة إلى نقد الروايات التاريخية عند علي أحمد باكثير وجرجي زيدان بين الصورة الفنية والموضوعية التاريخية، حيث تقوم الدراسة على المنهج التحليلي في معالجة العناصر الفنية للروايات التاريخية عند الأديبين، المتمثلة في صلاح الدين الأيوبي، وشجرة الدر، والحجاج بن يوسف لجرجي زيدان، ورواية وا إسلاماه، وسيرة شجاع، والفارس الجميل لعلي أحمد باكثير؛ وقد عني البحث بدراسة مجموعة من العناصر الروائية في الروايات المختارة، كأسلوب السرد، والزمان والمكان، والشخصيات، والمعطيات التاريخية، كما استعرضت الدراسة التقنيات الفنية لدى الروائيين في تنظيم المعطيات التاريخية، أما من حيث الموضوعية التاريخية فقد تطرقت الدراسة للمعطيات التاريخية عند الروائيين من حيث الحقيقة والخيال، وكيفية تعاملهما مع الوثائق التاريخية، وقد خلصت الدراسة إلى أن علي أحمد باكثير استأثر بالموضوعية على الصورة الفنية، بينما قدم جرجي زيدان الفن على حساب الموضوعية، كما أظهرت الدراسة أن باكثير اعتمد على فاعلية الشخصيات في بناء الرواية، بينما اعتمد زيدان على فاعلية المكان، وكلاهما قد حافظا على النتائج التاريخية المحسومة مع اختلافهما في كيفية سرد التاريخ وتفسيره. ************************************************************************************** The research seeks to critique the historical novels of the Ali Ahmad Bakathirand Jurji Zaydanbetween the artistic imageries and historical objectivity. Through the analytical approach the study will address the aesthetic elements of the historical novels of the writers as found in titles such as: "ØalÉÍal-DÊn al-Ayyūbi","ShajaratAl-Durr","Al-Hajjāj Bin YËsuf"; and "Wā IslÉmāh", "SÊrat al-ShujÉÒ", "Al-FÉris al-JamÊl", by Ali Ahmad Bakathir. The research is interested the fiction elements in selected novels, such as: narrative style, temporal element, personalities, historical data, and the aesthetical techniques of the writers in the organization of historical data. In terms of historical objectivity, the research has touched on the historical data as presented by the writers in terms of facts and fiction and the means through which they deal with historical documents. The research concluded that Bakathir was dedicated to objectivity but on the expense of the aesthetic image, while Zaydan was dedicated to the art but on the expense of objectivity. Bakathir also relied on the influence of the characters in the construction of the novel, while Zaydan relied on the influence of the place, both of which preserved historical results, but differed in the narration of history and its interpretation. *************************************************************************************** Kajian ini akan menkritik novel-novel sejarah yang dihasilkan oleh Ali Ahmad Bakathirand Jurji Zaydandari sudut nilai artistik dan objektiviti sejarah melalui kaedah analitikal yang akan menonjolkan elemen artistik dalam novel-novel sejarah oleh dua sasterawan ini dalam: "ØalÉÍal-DÊn al-Ayyūbi","ShajaratAl-Durr","Al-Hajjāj Bin YËsuf"; and "Wā IslÉmāh", "SÊrat al-ShujÉÒ", "Al-FÉris al-JamÊl", oleh Alī Aḥmad Bakathīr. Kajian ini akan mengkaji beberapa elemen naratif penceritaan dalam novel-novel dipilih ini seperti naratif, masa dan tempat, watak serta data sejarah. Kajian juga akan menunjukkan teknik-teknik seni kedua-dua novelis ini dalam menyusun data sejarah sama ada dari segi objektiviti sejarah, kebenarandan fiksyen, dan cara mereka bagi menangani dokumen-dokumen sejarah.Kajian mendapati bahawa Bakathir melebihkan objektiviti dari nilai artistik sebaliknya Zaydan nilai artistik dari objektiviti. Bakathir menumpukan kepada pengaruh karakter manakala Zaydan pulan menumpukan pengaruh tempat dalam membina penceritaan novel. Kedua-dua mereka masih menjaga sejarah walaupun berbeza cara penceritaan dan tafsiran sejarah.